Research on Some Key Problems of Self-exciting Electronic Ballast - Peng Mao; Weiping Zhang; Mao Zhang (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
on the analysis of operation principles of conventional self-exciting electronic ballast, the cause of high switching loss has been researched. In order to reduce switch temperature and increase the reliability of the whole circuit, drive circuit of self-exciting electronic ballast has been improved to achieve soft switch. Circuit simulations and experimental results are coincided with the analysis of theory. In the end of this paper, the design procedure and winding method of self-excited transformer are introduced.